2008
DOI: 10.1108/00035590810913097
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of polyaniline and poly(1‐naphthylamine) dispersed oil polyurethane coatings

Abstract: Purpose -The purpose of this paper is to report a comparative study of conducting polymer (CP) dispersed oil polyurethane coatings derived from a sustainable resource, i.e. polyaniline (PANI)/coconut oil polyesteramide urethane (CPEAU) and poly(1-naphthylamine) (PNA)/linseed oil polyurethane (LPUA) coatings. Design/methodology/approach -The coatings were prepared chemically and were characterized for their physico-chemical, physico-mechanical, corrosion protective efficiency, and open circuit potential measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The advantage of polyurethane coatings is their remarkable resistance to ultraviolet radiation and weather. Compared to epoxy coatings, they are also widely used for corrosion protection, 105,106 especially in an environment where sunlight is abundant, because this type of coating exhibits low loss of gloss and color change when exposed to ultraviolet radiation. 107 Due to good abrasion resistance, hardness, gloss, general chemical resistance, and impact resistance coupled with zero or low volatile organic compound (VOC) emissions, waterborne polyurethane dispersions are widely investigated.…”
Section: Polyaniline Polyurethane Coatings For Corrosion Inhibitionmentioning
confidence: 99%
“…The advantage of polyurethane coatings is their remarkable resistance to ultraviolet radiation and weather. Compared to epoxy coatings, they are also widely used for corrosion protection, 105,106 especially in an environment where sunlight is abundant, because this type of coating exhibits low loss of gloss and color change when exposed to ultraviolet radiation. 107 Due to good abrasion resistance, hardness, gloss, general chemical resistance, and impact resistance coupled with zero or low volatile organic compound (VOC) emissions, waterborne polyurethane dispersions are widely investigated.…”
Section: Polyaniline Polyurethane Coatings For Corrosion Inhibitionmentioning
confidence: 99%
“…Poly(urethane fatty amide) (PUFA) showed better coating performance in terms of gloss, bending, chemical resistance, impact resistance, scratch resistance, and thermal resistance. Ahmad et al, reported LO-based PUFA composite with conducting polymer, poly(1-naphthylamine) [ 113 ]. The dense and continuous structure of the tested coatings was consistent with their ability to protect the metal substrate from corrosion.…”
Section: Nonedible Vegetable Oil-based Polyurethane Coatingsmentioning
confidence: 99%
“…The dense and continuous structure of the tested coatings was consistent with their ability to protect the metal substrate from corrosion. The PUFA matrix functioned as a barrier coating and prevented the penetration of aggressive ions, while the conducting polymer reacted with the substrate to form a passive oxide layer [ 113 ]. NO fatty amide-based PU coatings showed good anticorrosive performance due to the excellent adhesion of the coatings with a metal substrate [ 119 ].…”
Section: Nonedible Vegetable Oil-based Polyurethane Coatingsmentioning
confidence: 99%